دور صفحات المرور في نشر الوعي المروري - أشواق شودار; إكرام قتال; د/هويشر مسعود (جامعة عمار ثليجي الاغواط, 2023)
ملخص الدراسة : هدفت دراستنا الى دور صفحات المرور في نشر الوعي المروري صفحة trafic ليتضح لنا مساهمة صفحة trafic Algérie في نشر الثقافة المروية لدى مستخدميها سواء السائقين او المشاة .. وايضا من ناحية الحملات التحسيسية التي تقوم عليها الصفحة من خلال توعية و نشر الاخبار حول السائقين او الحوادث المرورية وليس هذا فقط ايضا تقديم النصائح والإرشادات لمستخدمين الصفحة .. ولقد كان مستخدمي صفحة ترافيك الجيري المستهدف لدراستنا هذه حيث تطرقنا الى طرح التساؤل الرئيسي : كيف يتجسد دور صفحة طرافيك في نشرها الوعي المروري لدى السائقين؟ و اندرج تحت هذا التساؤل الرئيسي تساؤلات فرعية و هي كالتالي: -1هل تساهم صفحة طرافيك في تكوين ثقافة مرورية لدى السائقين ؟ -2هل تؤدي صفحة طرافيك دورا في نشر المعلومات والأخبار المتعلقة يحوادث السير ؟ حيث استخدمنا في دراستنا المنهج الوصفي وذلك لطبيعة الموضوع الذي يلائم هذا المنهج، كذلك تم استخدام أداة من أدوات جمع البيانات ألا وهي استمارة الكترونية والذي تضمن 20سؤال في محورين ، كما اعتمدنا على العينة القصدية التي شملت مستخدمي صفحة ترافيك الجيري. Study summary: Our study aimed at the role of the traffic pages in spreading traffic awareness, the trafic page, to make it clear to us the contribution of the trafic Algérie page in spreading the narratorial culture among its users, whether drivers or pedestrians..and also in terms of awareness campaigns on which the page is based by educating and spreading news about drivers or traffic accidents And this is not only providing advice and instructions to the users of the page.. The users of the Jerry Traffic page were the target of our study, as we touched on asking the main question: How is the role of the Trafik page embodied in spreading traffic awareness among drivers? Sub-questions were included under this main question: 1- Does your mobile page contribute to the formation of a traffic culture among drivers? 2- Does your mobile page play a role in publishing information and news related to traffic accidents? In our study, we used the descriptive approach due to the nature of the subject that fits this approach. An electronic form, which included 20 questions in two axes, was also used. We also relied on the intentional sample that included users of the Jerry Traffic page
trafic Algérie نموذج صفحة